Comparing the Use of Two Different Model Approaches on Students' Understanding of DNA Models - Julia Mierdel; Franz X. Bogner (MDPI AG, 2019)
As effective methods to foster students’ understanding of scientific models in science education are needed, increased reflection on thinking about models is regarded as a relevant competence associated with scientific literacy. Our study focuses on the influence of model-based approaches (modeling vs. model viewing) in an out-of-school laboratory module on the students’ understanding of scientific models. A mixed method design examines three subsections of the construct: (1) students’ reasoning about multiple models in science, (2) students’ understanding of models as exact replicas, and (3) students’ understanding of the changing nature of models. There were 293 ninth graders from Bavarian grammar schools that participated in our hands-on module using creative model-based tasks. An open-ended test item evaluated the students’ understanding of “multiple models” (MM). We defined five categories with a majority of students arguing that the individuality of DNA structure leads to various DNA models (modelers = 36.3%, model viewers = 41.1%). Additionally, when applying two subscales of the quantitative instrument Students’ Understanding of Models in Science (SUMS) at three testing points (before, after, and delayed-after participation), a short- and mid-term decrease for the subscale “models as exact replicas” (ER) appeared, while mean scores increased short- and mid-term for the subscale “the changing nature of models” (CNM). Despite the lack of differences between the two approaches, a positive impact of model-based learning on students’ understanding of scientific models was observed.